FORMATIVE ASSESSMENT AND FEEDBACK IN LANGUAGE LEARNING - Nomozova Nargiza Turayevna (Лучшие интеллектуальные исследования, 2024)
Abstract This article investigates the role of formative assessment and feedback in language learning. It explores the principles and practices of formative assessment, the importance of timely and constructive feedback, and the impact of these practices on language acquisition. The article discusses various formative assessment techniques, including quizzes, peer reviews, and self-assessment, and provides insights into how these can be effectively integrated into language teaching. The analysis highlights the benefits of formative assessment in promoting continuous improvement and fostering learner autonomy.